User Interface Improvement by Evaluating Usability and User Experience: Case Study of Indonesia’s Government Financial Management Information System - Fachri Munandar; Harry Budi Santoso (The Indonesian Journal of Computer Science, 2025)
SAKTI is an Enterprise Resource Planning (ERP) system developed by Indonesia’s Ministry of Finance, integrating 11 modules to support State Budget management. Despite its critical role, a decline in the 2023 user satisfaction index highlighted usability and service quality issues. This study offers user interface improvement by evaluating usability and user experience of the contract data recording feature. Using mixed methods, data from 23 respondents were collected for both quantitative and qualitative analysis. Quantitative data, obtained through the System Usability Scale (SUS) and User Experience Questionnaire (UEQ), yielded an initial SUS score of 67.39 (grade C) and a UEQ attractiveness index of 1.13. Qualitative data from open-ended questions, interviews, and usability testing identified 12 usability issues. A high-fidelity prototype, guided by User-Centered Design (UCD) principles, improved the SUS score to 84.35 (grade A+) and addressed usability challenges. It enhanced usability, creating an intuitive and efficient interface that increased user satisfaction.